(3TQM GdaUhd Gdegeg aj Yde ejQGK GdCeIs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s; (3GHf GdgGFe , TgGH GdOjf CHh GdYHGS GdefUhQj,J (B887 (3g` s ((3eMeO GdTGaYi s)
(3ChdgG (B:s
(3hHYO agPG JYdjb eNJUQ LYdJg TQMkG Ydi GdaUhd GdegeI ai ehGQjK GdCeI s
(3BNQgG (B:s
(3hGdeSGFd GdKdGK ef eSGFd GdeYGOI hai gPG GdYOO GdPi ChQOfGg caGjI Ef TGA Gddg JYGdi s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B220s
Keywords: (3Yde GdaQGFVs